Bleomycin and perioperative care: a case report - Jayakrishnan, B; Kausalya , Rajini; Al-Rashdi, Hilal A; Davis , Kirubakaran; Ali, Jahfar; Al-Harthy , Munjid; Bennji, Sami M (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Bleomycin is associated with pulmonary toxicity ranging from pneumonitis, pulmonary fibrosis, to fatal acute respiratory distress syndrome. Oxygen administration can potentiate or precipitate bleomycin pulmonary toxicity, and the most common setting of oxygen exposure is during anesthesia. We report here the successful management and perioperative care of a patient with documented bleomycin pulmonary toxicity who had to undergo an eight hour long retroperitoneal surgery. With proper preoperative assessment, chest physiotherapy, inhaled steroids and bronchodilators, antibiotics, operative restriction of oxygen and fluids and good postoperative care no further pulmonary insult was inflicted.